Effectiveness and safety of the Levitan FPS Scope™ for tracheal intubation under general anesthesia with a simulated difficult airway - Kok, Tracy; George, Ronald B.; McKeen, Dolores; Vakharia, Narendra; Pink, Aaron (Canadian journal of anesthesia, 2012)
Purpose Studies show that the Levitan FPS (first pass success) Scope™ (LFS) is analogous to a bougie in simulated difficult airways with comparable tracheal intubation success rates. In this study, the efficacy and safety of tracheal intubation with the LFS was compared with that of the Macintosh laryngoscope utilizing manual in-line stabilization (MILS) to simulate difficult airways. Methods Ninety-four subjects successfully completed the trial. Manual in-line stabilization of the cervical spine was applied and the initial laryngoscopy was performed using either the Macintosh or the LFS in conjunction with the Macintosh. Following the initial grading, a second laryngoscopy was repeated using the second randomized technique. Cormack-Lehane grades, percentage of glottic opening (POGO) scores, time to intubate, number of intubation attempts, and the use of alternate techniques were recorded. The anesthesiologist rated the subjective difficulty in using each technique with a numeric rating scale and a visual rating scale. Results There was no significant difference in the primary outcome “good laryngoscopic views” (Cormack-Lehane grade 1 and 2) compared with “poor laryngoscopic views” (Cormack-Lehane grade 3 and 4) between the LFS and the Macintosh. There were higher POGO scores with the LFS compared with the Macintosh (80% vs 20%, respectively; P < 0.0001), but this did not translate to easier intubations, as documented by the need for an alternate intubation technique or time to intubate (< 30 and < 60 sec, respectively). The incidence of mucosal trauma, sore throat, and hemodynamic responses did not differ significantly between the two techniques. Conclusion The LFS in conjunction with the Macintosh laryngoscope does not improve the efficacy or safety of tracheal intubation in a simulated difficult airway.